Kaposi Sarcoma Herpesvirus Inflammatory Cytokine Syndrome–like Clinical Presentation in Human Immunodeficiency Virus–infected Children in Malawi. (22nd March 2019) - El-Mallawany, Nader Kim; Kamiyango, William; Villiera, Jimmy; Peckham-Gregory, Erin C; Scheurer, Michael E; McAtee, Casey L; Allen, Carl E; Kovarik, Carrie L; Frank, Dale; Eason, Anthony B; Caro-Vegas, Carolina; Chiao, Elizabeth Y; et al.
Abstract: We describe 7 human immunodeficiency virus–infected Malawian children with Kaposi sarcoma who met criteria for Kaposi sarcoma herpesvirus (KSHV) inflammatory cytokine syndrome. Each presented with persistent fevers, bulky lymphadenopathy, massive hepatosplenomegaly, and severe cytopenias. Plasma analyses were performed in 2 patients, both demonstrating extreme elevations of KSHV viral load and interleukin 6.